A novel full soft-switching resonant power converter for mid-feeder voltage regulation of low voltage distribution network - Ji, Chao; Watson, Alan James; Clare, Jon C.; Johnson, Christopher Mark (2016)
This paper presents a novel resonant based, high power density power electronics converter solution for mid-feeder voltage regulation of a low voltage (LV) distribution network. Owing to the use of high switching frequency operation and a full soft-switching control strategy, the proposed converter is capable of superimposing LV compensation into the feeder voltage, to achieve a significant system effect with a compact system volume and correspondingly smaller absolute power loss.